New Electropositive Filter for Concentrating Enteroviruses and Noroviruses from Large Volumes of Water - Karim, Mohammad R. (American Society for Microbiology (ASM), 2009)
The U.S. Environmental Protection Agency's information collection rule requires the use of 1MDS electropositive filters for concentrating enteric viruses from water, but unfortunately, these filters are not cost-effective for routine viral monitoring. In this study, an inexpensive electropositive cartridge filter, the NanoCeram filter, was evaluated for its ability to concentrate enteroviruses and noroviruses from large volumes of water. Seeded viruses were concentrated using the adsorption-elution procedure. The mean percent retention of seeded polioviruses by NanoCeram filters was 84%. To optimize the elution procedure, six protocols, each comprising two successive elutions with various lengths of filter immersion, were evaluated. The highest virus recovery (77%) was obtained by immersing the filters in beef extract for 1 minute during the first elution and for 15 min during the second elution. The recovery efficiencies of poliovirus, coxsackievirus B5, and echovirus 7 from 100-liter samples of seeded tap water were 54%, 27%, and 32%, respectively. There was no significant difference in virus recovery from tap water with a pH range of 6 to 9.5 and a water flow rate range of 5.5 liters/min to 20 liters/min. Finally, poliovirus and Norwalk virus recoveries by NanoCeram filters were compared to those by 1MDS filters, using tap water and Ohio River water. Poliovirus and Norwalk virus recoveries by NanoCeram filters from tap and river water were similar to or higher than those by the 1MDS filters. These data suggest that NanoCeram filters can be used as an inexpensive alternative to 1MDS filters for routine viral monitoring of water.